Effect of physical activity on the severity of irritable bowel syndrome (IBS) symptoms - Machała-Ćwikła, Ewelina; Łapińska, Urszula; Zdziebło , Piotr; Ćwikła, Piotr; Machała, Kamila; Szeląg, Kacper; Machala, Dominika; Kujawski, Antoni; Zuzak, Andrzej Paweł; Zdziebło, Katarzyna (Quality in Sport, 2024)
Irritable bowel syndrome is a chronic gastrointestinal disease whose symptoms affect patients’ daily lives. Exacerbation of symptoms can worsen patients’ quality of life and lead to depressive-anxiety and somatoform disorders. The associated costs burden not only the patients, but also those around them. The etiology of IBS is multifactorial and not fully understood. The brain-gut axis remains a subject of research, which may involve the development of new, effective therapies for the treatment of IBS in the future. Pharmacological and non-pharmacological methods are used to treat IBS. In order to provide the patient with the best possible treatment results in the absence of significant side effects, research is being conducted on the possibilities of non-pharmacological patient management. Currently, there are numerous studies on the effect of physical activity on the severity of symptoms in IBS patients. The results show that the introduction of moderate-intensity physical activity has positive effects in terms of alleviating gastrointestinal symptoms, reducing the severity of psychological and somatoform symptoms, and improving patients’ well-being as well as quality of life. Appropriate physical activity is acceptable to patients and rated by them as positive and having a beneficial effect on IBS symptoms. The lack of patient-reported significant side effects is important. Given the results of the study, it seems beneficial to recommend that IBS patients perform moderate physical activity to alleviate and control symptoms. It is necessary to educate patients and individualize physical activity recommendations to match the type of activity to patients’ abilities and needs.